2017
DOI: 10.1093/infdis/jiw520
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dedicated Mobile Teams and Polio Volunteer Community Mobilizers to Increase Access to Zero-Dose Oral Poliovirus Vaccine and Routine Childhood Immunizations in Settlements at High Risk for Polio Transmission in Northern Nigeria

Abstract: BackgroundThe Polio Eradication Initiative in Nigeria, which started >20 years ago, faced many challenges, including initial denial, resistance from communities, and prolonged regional safety concerns. These challenges led into the structuring of the response including the development of the National Emergency Action Plan, improved partner coordination and government engagement, and the establishment of a Polio Emergency Operations Centre. Although monthly supplementary immunization activities (SIAs) continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Three systematic reviews have reported important effects of MCH outreach delivery strategies on MCH service provision in non-emergency areas 24–26. Three additional studies have reported important impacts on MCH service delivery in conflict settings 8–10. In Myanmar, specialised maternal services in border camps increased ANC and PNC by 32%–50% 9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three systematic reviews have reported important effects of MCH outreach delivery strategies on MCH service provision in non-emergency areas 24–26. Three additional studies have reported important impacts on MCH service delivery in conflict settings 8–10. In Myanmar, specialised maternal services in border camps increased ANC and PNC by 32%–50% 9.…”
Section: Discussionmentioning
confidence: 99%
“…Polio campaign camps in conflict-affected areas of Pakistan increased vaccination rates by 7%–9% 10. Regular visits from a MHT programme funded by the Polio programme in Nigeria increased coverage of children ‘fully immunised’ by 33%–36% 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the articles in this supplement take stock of how GPEI resources support RI activities and contribute to strengthening RI services, with the specific aim of identifying services that may be at risk when polio resources diminish after eradication [80,81]. Deutsch et al and Ongwae et al describe how use of polio resources, social mobilization networks, and experience may also be valuable to broader health programs and RI activities [82,83]. Van den Ent et al identify several key factors behind the success of polio eradication programs in the 10 high-risk priority countries, including government leadership, evidence-based programing, community partnership, and strong accountability systems [84].…”
Section: Strengthening Immunization Servicesmentioning
confidence: 99%
“…When Ebola virus was detected in Nigeria, the emergency operations center capability that had been put in place to manage the polio program was quickly repurposed to manage the Ebola outbreak, which was quickly terminated. GPEI-funded assets are also working to strengthen routine immunization in Nigeria [ 23 ]. The National Stop Transmission of Polio program, for example, was created in 2012 with the support of the Centers for Disease Control and Prevention and now involves >180 officers posted across the country.…”
Section: Transition Planning Processmentioning
confidence: 99%